MENINGKATKAN HASIL BELAJAR IPA SISWA SMA LB PADA MATERI POKOK SUMBER ENERGI DAN KEGUNAANNYA MELALUI MODEL PEMBELAJARAN DIRECT INSTRUCTION - Puji Astuti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
Has done research on the learning outcomes of Natural Sciences on the material and its use by using direct instruction teaching model. The purpose of this research is to improve student learning outcomes on the material source of energy and usefulness. Study consisted of two cycles, it is expected through increasing of learning activities. Finally, student’s learning outcomes will increase. Subject of this research is students of SMALB Tanjung Pelita Hati 10th grade amounted 5 people. research results can be obtained from the test giving and deployment of questionnaire. The results showed that: (1). The ability of teachers to implement design of learning (RPP) in teaching at the first cycle was 96.87% and the second cycle teachers can implement learning activities in accordance with the design of learning full, (2). Student learning activities in the first cycle, the percentage of students who are active around 80.00 to 100% and the second cycle of active students ranged from 90.00% to 100%. (3). The results of student learning in the first cycle an average of 62.00% and 60.00% exhaustiveness classical, and the second cycle has increased to 72.00% and 80.00% exhaustiveness classical, (4). The student’s responses of the learning activities is positive.Key words: direct instruction teaching model, Natural Sciences, material source of energy and usefulness